Secretory carcinoma — impact of translocation and gene fusions on salivary gland tumor - Inaki, Ryoko (Chin J Cancer Res, 2017)
Secretory carcinoma (SC), previously described as mammary analogue secretory carcinoma (MASC), is a recently described salivary gland tumor which morphologically resembles mammary secretory carcinoma. The first description of SC/MASC, reported by Skálová et al. in 2010, was as a rare salivary carcinoma imitating secretory carcinoma of the breast. SC/MASC is a unique salivary gland tumor with morphological overlap with acinic cell carcinoma (AciCC), mucoepidermoid carcinoma (MEC), and adenocarcinoma not otherwise specified (ADC-NOS). SC/MASC shares similar clinicopathological features with AciCC. As a critical difference between SC/MASC and AciCC, SC/MASC characteristically has the chromosomal translocation t(12;15)(p13;q25) which leads to a fusion gene between the ETV6 gene on chromosome 12 and the NTRK3 gene on chromosome 15. This genetic background is an important differential diagnostic finding for excluding other salivary gland tumors and may be a critical factor determining the prognosis for patients with SC/MASC. Research in recent years has provided a large body of new data on SC/MASC and suggests the possibility that the ETV6-NTRK3 translocation could be a therapeutic target. Here, we review the morphological and clinicopathological features of SC/MASC and discuss new directions for therapy.